Development and performance evaluation of two-row tyned weeder for weed management in maize crop - Gatkal, Narayan R.; Nalawade, Sachin M.; Shelke, Mohini S.; Sahni, Ramesh K.; Adedeji, Akinbode A.; Najser, Tomáš; Beňová, Kateřina (International Journal of Agricultural and Biological Engineering, 2025)
Weeds significantly reduce crop yield (34%) as compared to pests (18%) and pathogens (16%). Also, weeds are one of the most significant biotic factors contributing to declining yield. Various methods are used to control weeds in row crops. Traditional methods like manual weeding are time-consuming, labor-intensive, and tedious. Chemical treatment with use of herbicides is not eco-friendly. In view of all the above problems, a two-row tyned weeder was developed for managing weeds in row crops. The developed weeder consists of a main frame, engine, tyne, wheel, and handle. Response surface methodology (RSM) along with the central composite design was used to study the effect of independent variables of forward speed (1.5, 2, and 2.5 km/h) and moisture content of soil (12%, 14%, and 16% (w.b.)) on response variables for the purpose of optimizing the operational parameters of the two-row tyned weeder. The optimized parameters for tyned weeder are forward speed of 2 km/h and moisture content of 14%. The weeding efficiency, plant damage, and field efficiency were 88.38%, 6.46%, and 81.66%, respectively, at optimized parameters. The performance parameters such as field capacity, depth, and width of operation were 0.08 hm2/h, 55 mm, and 600 mm, respectively. The savings in cost of operation and labor for the developed two-row tyned weeder over the manual hand wheel hoe were 76.11% and 92.86%, respectively. The payback period, break-even point, labor requirement, and performance index for the developed two-row tyned weeder were 1.12 a, 104.5 h/a, 10.35 man-h/hm2, and 410.91, respectively. Keywords: field efficiency, maize, optimization, plant damage, RSM, weeder, weeding efficiency DOI: 10.25165/j.ijabe.20251804.9652Citation: Gatkal Narayan R, Nalawade Sachin M, Shelke Mohini S, Sahni Ramesh K, Adedeji Akinbode A, Najser T, et al. Development and performance evaluation of two-row tyned weeder for weed management in maize crop. Int J Agric & Biol Eng, 2025; 18(4): 170–180.